Using DGPS to Measure the Heave Motion of Hydrographic Survey Vessels - Kielland, Peter; Hagglund, John (The International Hydrographic Review, 2015)
One quite significant error source encountered by hydrographers is wave induced vertical motion of their survey vessel (heave). In heavy swells, uncorrected heave noise will degrade the accuracy of the surveyed soundings upon which mariners rely for safe navigation. Heave motion can be measured using inertial technology thus enabling the raw surveyed soundings to be corrected to calm water conditions. Unfortunately, the high cost of inertial heave compensators has prohibited their widespread use. This paper documents a test carried out by the Canadian Hydrographic Service in which very accurate relative position derived from GPS phase observations were used to determine heave corrections for a hydrographic survey vessel. The algorithm is simply a high pass filter acting on the unused DGPS vertical position record already being observed on the vessel. An inexpensive pitch and roll inclinometer is used to correct for the lever arm effect between the GPS antenna and the sounder’s transducer. The experiment indicated that decimetre heave compensation accuracy was obtained.